Growth Opportunities, Earnings Permanence and the Valuation of Free Cash Flow - Ahsan Habib (Australasian Accounting, Business and Finance Journal, 2012)
This paper examines empirically the effect of firm growth opportunities and earnings quality on the market valuation of free cash flow, defined as the difference between operating cash flows and capital expenditures. Equity valuation theory prescribes that free cash flow should not be associated with stock returns because it does not add value. However, free cash flow could become a value-relevant construct in certain contexts. This study considers growth opportunities and transitory earnings as two such contexts and examines the valuation of free cash flow. An accounting-based valuation framework is developed where stock returns are regressed on free cash flow interacted with growth and earnings quality proxies, after controlling for book values, dividends, and current earnings realisations. Findings reveal that firms with a positive free cash flow and attractive growth opportunities command a valuation premium. Furthermore, free cash flow is found to be positively associated with stock returns when earnings are transitory. The results are robust to alternative definitions of both free cash flow and growth opportunities.
Keywords: Free cash flow; agency theory; growth opportunities; earnings quality